NEW VIENNA SCHOOL (Conferencea, 2023)
In this article, the role of modern music in the art of music, representatives of the new Vienna school, modern music and its aesthetic education in human psychology, the development of all types of creativity, increasing self-confidence, the main aesthetic directions, currents of neoclassicism , modernism, dodecophonism, invaluable works of composers during the analysis of their views on the role and problems of music development in this direction, the views of our scientists, the enthusiasm of historical processes also influenced the development of art.